Formulation of Exchange Rate Policies in Adjustment Programs. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1985)
The role of exchange rate policy in economic adjustment has been widely studied and is the subject of numerous theoretical and empirical papers produced in the Fund and elsewhere.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet